Bangun Citra, Kuatkan Usaha: Workshop Strategi Branding Sebagai Upaya Pemberdayaan UMKM Kelurahan Rangkah: Penelitian - Ardiella Sukma Maheswari; Cahya Yuhan Armandha; Elvina Rahma Khairunnis; Mohammad Syarrafah (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The Thematic Community Service Program (KKNT) on State Defense and SDGs Period II conducted by Universitas Pembangunan Nasional “Veteran” Jawa Timur in Rangkah Village aimed to empower the local community by strengthening the capacity of Micro, Small, and Medium Enterprises (MSMEs). This program focused on enhancing participants’ understanding and skills in building effective branding strategies through a workshop titled “Build Image, Strengthen Business.” The implementation methods included lectures, tutorials, discussions, and follow-up mentoring sessions. The results indicated a significant increase in participants’ knowledge regarding the importance of brand image, promotional strategies, and the utilization of social media as a digital marketing tool. Participants began to apply the knowledge gained by rebranding their logos, improving packaging design, and strengthening their product visual identity. This activity had a positive impact on improving the competitiveness and professionalism of MSME actors in Rangkah Village. Therefore, this program contributes to achieving Sustainable Development Goal (SDG) 8, which focuses on decent work and economic growth.